2021
DOI: 10.3390/ijms221910504
|View full text |Cite
|
Sign up to set email alerts
|

Helium Conditioning Increases Cardiac Fibroblast Migration Which Effect Is Not Propagated via Soluble Factors or Extracellular Vesicles

Abstract: Helium inhalation induces cardioprotection against ischemia/reperfusion injury, the cellular mechanism of which remains not fully elucidated. Extracellular vesicles (EVs) are cell-derived, nano-sized membrane vesicles which play a role in cardioprotective mechanisms, but their function in helium conditioning (HeC) has not been studied so far. We hypothesized that HeC induces fibroblast-mediated cardioprotection via EVs. We isolated neonatal rat cardiac fibroblasts (NRCFs) and exposed them to glucose deprivatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 48 publications
0
7
0
Order By: Relevance
“…After treatment of THP-1-ASC-GFP cells as described above, cells were lyzed in quiazol lysis reagent (Quiagen, Germantown, MD, USA) and stored at − 80 °C. Total RNA isolation, cDNA synthesis and qPCR measurements were performed as described earlier 86 . Measurements were performed on a LightCycler 480 Real-Time PCR System (Roche Diagnostics, Basel, Switzerland) using LightCycler ® RNA Master SYBR Green I reagent (Roche Diagnostics, Basel, Switzerland) with primers presented in Supplementary Table S2 , with the following protocol: Initiation: 95 °C 2 min; Amplification: (45x) 95 °C 5 s, 57 °C 10 s, 72 °C 20 s. Data were analyzed by ΔΔCt calculation method according to Schmittgen and Livak 2008 87 , using Hypoxanthine Phosphoribosyltransferase 1 (HPRT) as a housekeeping gene.…”
Section: Methodsmentioning
confidence: 99%
“…After treatment of THP-1-ASC-GFP cells as described above, cells were lyzed in quiazol lysis reagent (Quiagen, Germantown, MD, USA) and stored at − 80 °C. Total RNA isolation, cDNA synthesis and qPCR measurements were performed as described earlier 86 . Measurements were performed on a LightCycler 480 Real-Time PCR System (Roche Diagnostics, Basel, Switzerland) using LightCycler ® RNA Master SYBR Green I reagent (Roche Diagnostics, Basel, Switzerland) with primers presented in Supplementary Table S2 , with the following protocol: Initiation: 95 °C 2 min; Amplification: (45x) 95 °C 5 s, 57 °C 10 s, 72 °C 20 s. Data were analyzed by ΔΔCt calculation method according to Schmittgen and Livak 2008 87 , using Hypoxanthine Phosphoribosyltransferase 1 (HPRT) as a housekeeping gene.…”
Section: Methodsmentioning
confidence: 99%
“…Primary neonatal rat hearts were isolated from 1–3-day-old Wistar rats (~3–4 animal/24-well plate) as previously described [ 31 ]. Briefly, rats were disinfected with 70% ethanol and sacrificed by cervical dislocation.…”
Section: Methodsmentioning
confidence: 99%
“…Scratch assays were performed as reported previously [ 31 ]. Briefly, cells were seeded on 24-well plates, and were pretreated with 500 nM saxagliptin or its solvent for 1 h. After pretreatment, the cell monolayer was scratched with a 200 µL pipette tip in a 30° angle.…”
Section: Methodsmentioning
confidence: 99%
“…In contrast to the healthy Wistar Kyoto rats (WKRs), only a triple intervention of He conditioning can reduce cell damage after myocardial I/R in spontaneous hypertensive rats (SHR), suggesting the presence of a threshold in the hypertensive heart ( 54 ) ( Table 1 ). An in-vitro study indicated that He conditioning contributed to cardioprotection by increasing fibroblast migration, but not by releasing protective medium extracellular vesicles or soluble factors from the cardiac fibroblasts ( 88 ). Our recent study indicated that intraperitoneal injection of 99.999% He gas improved lipopolysaccharide (LPS)-induced left ventricular dysfunction and cavity enlargement in a dose-dependent manner, it is better at the dose of 1.0 ml/100 g ( 89 ).…”
Section: Noble Gases: the “New World” Of Cardiocerebrovascular Protec...mentioning
confidence: 99%